Struktur Belanja Rumah Tangga Petani Padi di Kabupaten Tegal - Mirza Andrian Syah; Ida Syamsu Roidah; Ika Sari Tondang (JURNAL MANAJEMEN AGRIBISNIS, 2022)
The condition of the COVID-19 pandemic has forced farmers to adopt some new habits so that household income and expenses may differ between before and after the pandemic. This study was aimed to analyze the total income and expenditure of rice farmers' households and analyze several factors that can affect the total expenditures of rice farmers' households. This research was conducted in Dukuhwaru District, Tegal Regency. The method used in this study was the survey method by taking several samples from members of the existing farmer population. The results showed that the total household income of rice farmers in Dukuhwaru District was IDR 44,944,892.37 per year. The total household expenditure of rice farmers was IDR 17,963,720.00 per year allocated 57.49% from food consumption and 42.51% from non-food consumption. Factors that affect rice farmers' household expenditures were the area of rice fields, the number of family members, and the number of school children. The COVID-19 pandemic does not affect farmers in Dukuhwaru District to keep farming three times a year but increases household spending on electricity and education costs.